Description Of Factors In The Utilization Of Mental Health Services at Sambang Lihum Mental Health Hospital In South Kalimantan - Naediwati, Ema Dessy; Syamsudin, Achmad (Jurnal Keperawatan Universitas Jambi, 2025)
Mental disorders are increasing worldwide. Most cases of mental disorders go untreated. Several studies have shown that there are factors associated with the utilization of mental health services. The most important factors are stigma, feelings, lack of knowledge, available mental health services, personal beliefs, and social support. Sambang Lihum Mental Health Hospital is a very potential research site to obtain research results that represent mental health services in the province of South Kalimantan. The purpose of this study was to identify a description of factors in the utilization of mental health services at Sambang Lihum Mental Health Hospital. This study was a quantitative descriptive study with 111 respondents selected using a purposive sampling technique conducted in the psychiatry and drug polyclinic of Sambang Lihum Mental Health Hospital. Data were analyzed using univariate analysis. The results of this study indicate that the most important factors in utilizing mental health services are stigma, feelings, lack of knowledge, available mental health services, personal beliefs, and social support. Most respondents sought treatment at mental health services within a duration of 3 months to 1 year after the first symptoms of mental disorders appeared. Mental health service providers are expected to be able to educate about mental disorders and treatment so that they can increase patient and family awareness to utilize mental health services.